A pathogenicity determinant maps to the N‐terminal coat protein region of the Pepino mosaic virus genome. (9th October 2014) - Duff‐Farrier, Celia R. A.; Bailey, Andy M.; Boonham, Neil; Foster, Gary D.
Summary Pepino mosaic virus (PepMV) poses a worldwide threat to the tomato industry. Considerable differences at the genetic level allow for the distinction of four main genotypic clusters; however, the basis of the phenotypic outcome is difficult to elucidate. This work reports the generation of wild‐type PepMV infectious clones of both EU (mild) and CH2 (aggressive) genotypes, from which chimeric infectious clones were created. Phenotypic analysis in three solanaceous hosts, Nicotiana benthamiana, Datura stramonium and Solanum lycopersicum, indicated that a PepMV pathogenicity determinant mapped to the 3′‐terminal region of the genome. Increased aggression was only observed in N. benthamiana, showing that this factor is host specific. The determinant was localized to amino acids 11–26 of the N‐terminal coat protein (CP) region; this is the first report of this region functioning as a virulence factor in PepMV.